Rationale and design of the coronary artery bypass grafting surgery off or on pump revascularization study: a large international randomized trial in cardiac surgery. - Lamy, A; Devereaux, P; Prabhakaran, D; Hu, S; Piegas, L; Straka, Z; Paolasso, E; Taggart, D; Lanas, F; Akar, A; Jain, A; Noiseux, N; et al. (2012)
BACKGROUND: Uncertainty remains regarding the benefits and risks of the technique of operating on a beating heart (off pump) for coronary artery bypass grafting (CABG) surgery versus on-pump CABG. Prior trials had few events and relatively short follow-up. There is a need for a large randomized, controlled trial with long-term follow-up to inform both the short- and long-term impact of the 2 approaches to CABG. METHODS: We plan to randomize 4,700 patients in whom CABG is planned to undergo the procedure on pump or off pump. The coprimary outcomes are a composite of total mortality, myocardial infarction (MI), stroke, and renal failure at 30 days and a composite of total mortality, MI, stroke, renal failure, and repeat revascularization at 5 years. We will also undertake a cost-effectiveness analysis at 30 days and 5 years after CABG surgery. Other outcomes include neurocognitive dysfunction, recurrence of angina, cardiovascular mortality, blood transfusions, and quality of life. RESULTS: As of May 3, 2011, CORONARY has recruited >3,884 patients from 79 centers in 19 countries. Currently, patient's mean age is 67.6 years, 80.7% are men, 47.0% have a history of diabetes, 51.4% have a history of smoking, and 34.4% had a previous MI. In addition, 20.9% of patients have a left main disease, and 96.6% have double or triple vessel disease. CONCLUSIONS: CORONARY is the largest trial yet conducted comparing off-pump CABG to on-pump CABG. Its results will lead to a better understanding of the safety and efficacy of off-pump CABG.